2015
DOI: 10.1093/neuonc/nov104
|View full text |Cite
|
Sign up to set email alerts
|

Randomized phase 2 study of carboplatin and bevacizumab in recurrent glioblastoma

Abstract: ACTRN12610000915055.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
89
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 138 publications
(103 citation statements)
references
References 29 publications
9
89
3
2
Order By: Relevance
“…Toxicity of bevacizumab was mainly non-hematologic including hypertension, thrombembolic events, fatigue, and impaired wound healing. Overall response rates were similar in most trials with around one third of the patients mainly assessed by Macdonald criteria but also by RANO [54,90], while one trial only reports 6%, assessed by RANO criteria [84]. PFS-6 rates ranged from 18% to 42.6% and median OS from 6.5 to 9.2 months.…”
Section: Other Classical Non-alkylating Chemotherapymentioning
confidence: 86%
See 3 more Smart Citations
“…Toxicity of bevacizumab was mainly non-hematologic including hypertension, thrombembolic events, fatigue, and impaired wound healing. Overall response rates were similar in most trials with around one third of the patients mainly assessed by Macdonald criteria but also by RANO [54,90], while one trial only reports 6%, assessed by RANO criteria [84]. PFS-6 rates ranged from 18% to 42.6% and median OS from 6.5 to 9.2 months.…”
Section: Other Classical Non-alkylating Chemotherapymentioning
confidence: 86%
“…A detailed listing of all trials with these agents, mostly conducted as single arm studies, would be beyond the scope of this review. Carboplatin (CABARET trial) and irinotecan (BRAIN trial) have been evaluated in randomized phase II trials as add-ons to bevacizumab (Table 3) [84,85]. Both trials were negative showing no difference in outcome but additional toxicity in the treatment arms with carboplatin and irinotecan.…”
Section: Other Classical Non-alkylating Chemotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…32,[59][60][61][62][63][64][65][66][67][68] The randomized phase 2 GLARIUS trial compared bevacizumab, irinotecan, and radiotherapy versus standard temozolomide and radiation in patients with O 6 -methylguanine-methyltransferase (MGMT)-unmethylated, newly diagnosed glioblastoma. 59 This study found the combination of bevacizumab and irinotecan with radiotherapy to be more favorable than standard therapy, with the 6-month PFS rate reported at 79.5% versus 41.3%, and a mean PFS of 9.7 months versus 6 months, respectively.…”
Section: Newly Reported Bevacizumab Trialsmentioning
confidence: 99%